2018
DOI: 10.1097/bor.0000000000000500
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine: balancing the need to maintain therapeutic levels with ocular safety: an update

Abstract: The most important changes in practice guidelines include dose calculation based on total body weight, dose reduction after long-term use, and intensified screening with techniques including optical coherence tomography (OCT) after 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 38 publications
1
24
0
1
Order By: Relevance
“…Rigorous pharmacoepidemiologic studies are needed to ascertain potential benefits of HCQ in TID. In addition, the appropriate dosing, as well as relative risks and benefits of long term HCQ use should be carefully assessed considering the concerns for ocular toxicity, especially in individuals with impaired kidney function (20). Whether longitudinally HCQ use results in less IF/TA deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…Rigorous pharmacoepidemiologic studies are needed to ascertain potential benefits of HCQ in TID. In addition, the appropriate dosing, as well as relative risks and benefits of long term HCQ use should be carefully assessed considering the concerns for ocular toxicity, especially in individuals with impaired kidney function (20). Whether longitudinally HCQ use results in less IF/TA deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors have been shown to affect blood levels of HCQ, such as genetic variants of the CYP enzyme family, age, gender, body weight, gastric emptying, and co-administration with immunosuppressants, such as corticosteroids (Al-Rawi et al., 2018 ; Lee et al., 2016 , 2017 ). Even though it has been reported that renal clearance of unchanged drug was approximately 16 to 30% and did not correlate with creatinine clearance (Miller et al., 1991 ), renal insufficiency has been reported to increase the risk of toxicity (Abdulaziz et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…In view of the above, HCQ levels of 2250 ng/ml, even though rather conservatory, were used as an upper limit, considering also the cardiotoxic effects of the drug, possible co-administered medications and impaired clearance due to co-morbidities (Abdulaziz et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Four additional models describe plasma concentrations or merged blood and plasma concentrations. [16][17][18][19] Blood concentrations are known to be more reproducible (because higher, with lesser analytical sensitivity issues). We therefore used the model by Carmichael et al 3 for subsequent simulation after independent validation.…”
Section: Wha This Study Addsmentioning
confidence: 99%